183 Low-grade hypertension and coronary atherosclerosis in male master endurance athletes. (4th June 2021) - Parry-Williams, Gemma; Obaid, Daniel; Moser, Joanna; Vlahos, Ioannis; Bulleros, Paulo; Fanton, Zephryn; Basu, Joyee; Miles, Christopher; MacLachlan, Hamish; Moreira-Accame, Max; Bakalakos, Athanasios; Hisham, Idura Binti Ikmal; et al.
Abstract : Background: Ostensibly healthy male master endurance athletes have a greater prevalence of high coronary calcium (CAC) scores and coronary artery plaque burden, compared to similar aged, healthy sedentary counterparts. A number of theories have been postulated but reasons remain unclear. Hypertension is the leading cardiovascular risk factor in the general population. The role of subclinical hypertension and the hypertensive response to exercise (HRE) in the pathophysiology of high CAC scores and other CT markers of high-risk coronary artery disease, has not previously been reported in the healthy master endurance athlete population. Methods: A cohort of 214 low Q-risk, male master (40-65 years) endurance athletes were prospectively evaluated between February 2018 and September 2019. All athletes were free from any cardiovascular risk factors, symptoms and any relevant health conditions. Clinical evaluation included cycle ergometer cardiopulmonary exercise test, ambulatory BP monitoring and coronary computed tomogram angiography (CCTA). The CCTA assessed CAC score, coronary stenosis, defined as >50%, plaque morphology (i.e. calcified, soft or mixed), and markers of plaque vulnerability including spotty calcification, ruptured plaque, positive remodelling, low attenuation plaque and napkin ring sign. Resting BP, HRE and ambulatory hypertension were defined in accordance with the latest European Society of Cardiology (ESC) guidelines and are detailed in table 1 . Results: All athletes (mean age 51, SD 70.1) exercised for at least 6 hours per week (median 8.5 hours) for a median of 15 years of either cycling, running or swimming or any combination of the three. The median Q risk score was 3.5%. A quarter (26%) of athletes were hypertensive at rest. A significant proportion of athletes exhibited exercise (12%) and ambulatory hypertension (41%). A CAC score >100 Agatston units (AU) was present in (16%) of athletes, with 5% exhibiting significant coronary stenosis. A third (32%) of all plaque morphologies were non-calcified (27% mixed and 5% soft) and 13% had additional plaque vulnerability markers. The most prevalent marker was spotty calcification (11.3%), followed by positive remodelling (8.9%). Logistic regression identified the BP parameters predictive for a CAC score >100 AU, significant stenosis and plaque vulnerability markers. A 5 mmHg increase in resting systolic BP, maximal systolic exercise BP and 24 hour and nocturnal ambulatory systolic were associated with both significant stenosis and plaque vulnerability markers and a 5 mmHg increase in resting systolic BP (SBP) and 24 hour and nocturnal ambulatory SBP were associated with a CAC score >100 AU. The p values, odds ratios (OR) and respective 95% confidence intervals are detailed in table 3 . BP parameters were not associated with calcified plaque by multinomial logistic regression, however for every 5mmHg increase in maximal exercise SBP, resting SBP and 24-hour and nocturnal ambulatory SBP, the relative risk (RR) of mixed morphology plaque was increased by 19.27% (p=0.001, CI 1.07-1.33), 18.49% (p=0.024, CI 1.02-1.37), 46.45% (p=0.001, CI 1.12-1.91) and 50.54% (p=0.001, CI 1.18-1.93) respectively. Conclusions: Hypertension is prevalent, under diagnosed, and contributes to the development of potentially unstable coronary artery disease in healthy male endurance athletes. Recommendations for cardiovascular evaluation of master athletes should consider a low threshold for non-invasive exercise testing and ambulatory BP monitoring for for athletes with hypertension and even high-normal BP. Table 1 . ESC definitions of hypertension. Table 2 . Prevalence of hypertension according to ESC guideline classifications. Table 3 . Logistic regression P values, odds ratios and confidence intervals for a 5mmHg increase in BP parameters. Conflict of Interest: Nil